2018
DOI: 10.3389/fpsyg.2018.01345
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Compromise of Nouns and Action Verbs in Posterior Cortical Atrophy

Abstract: Processing of nouns and action verbs can be differentially compromised following lesions to posterior and anterior/motor brain regions, respectively. However, little is known about how these deficits progress in the course of neurodegeneration. To address this issue, we assessed productive lexical skills in a patient with posterior cortical atrophy (PCA) at two different stages of his pathology. On both occasions, he underwent a structural brain imaging protocol and completed semantic fluency tasks requiring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…A language profile similar to that seen in people with logopenic aphasia was reported in three studies, 83,84,85 but with milder impact on comprehension and spontaneous speech 84 . One paper highlighted impaired fluency for nouns and verbs 86 . The remaining three studies identified additional impairments in comprehending words related to space and quantity 64,87,88 …”
Section: Resultsmentioning
confidence: 52%
“…A language profile similar to that seen in people with logopenic aphasia was reported in three studies, 83,84,85 but with milder impact on comprehension and spontaneous speech 84 . One paper highlighted impaired fluency for nouns and verbs 86 . The remaining three studies identified additional impairments in comprehending words related to space and quantity 64,87,88 …”
Section: Resultsmentioning
confidence: 52%
“…Finally, due to practical limitations, behavioral and neuroimaging analyses were here performed on two separate samples, which precluded the exploration of correlations between performance and neural signatures. Although this methodology has yielded informative results regarding other aspects of language 121 , it would be desirable to circumvent such a limitation in new studies.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found ( F 1,42 = 0.00, p = .992, ηp 2 < 0.01) between patients ( M = 1,386.73, SD = 128.83) and controls ( M = 1,386.35, SD = 122.66). Statistical significance was set at p < .001 uncorrected, extent threshold = 30 voxels (de la Fuente et al., 2019; Steeb et al., 2018). A power estimation analysis confirmed the robustness of our results (Information S2).…”
Section: Methodsmentioning
confidence: 99%